'Artefactual co-creations': Developing practice-based research with Somali women in a third sector family literacy class. Issue 2 (3rd July 2021) - Puttick, Mary-Rose
Abstract: This paper centres on a methodological approach that drew together postcolonial feminist theory with arts-based methods, as well as learning from Indigenous methodologies. The methodology developed over 2 years with two groups of women from refugee and newly arrived migration contexts. This paper focuses on the co-created research process with one of the groups: six Somali women who attended a family literacy class at a third sector organisation in Birmingham, UK. An exploratory literacy space was established, with no set curriculum or links to school-based assessment measures, as a purposeful diversion from the researcher-teacher's previous teaching practice in government-funded family literacy provision. Using artefacts, the women mobilised the methodological direction of the research into affectual and sensory aspects, culminating in a 'pedago-Vis-ual' assemblage. The research contributes theoretical and methodological aspects to the fields of family literacy, literacy, and practice-based research. Theoretically, the paper expands understanding of family literacy teaching and learning in the 'posts': transitioning from Western-dominated definitions of family literacy from its traditional humanist roots towards post-human ways of knowing, the latter led by women who are potentially isolated from traditional educational provision. Methodologically, the paper mobilises ways that arts-based methods can be combined with learning from Indigenous principles to foreground the voices of politically marginalised groups and the reciprocity and respect that must accompany this.